Programmed cell death in sympathetic neurons: a study by two-dimensional polyacrylamide gel electrophoresis using computer image analysis. - Amess, B; Tolkovsky, A (1995)
The technique of two-dimensional polyacrylamide gel electrophoresis (2-D PAGE) coupled with computer image analysis was used in this study to examine changes in protein expression occurring during the onset of programmed cell death (PCD) in rat sympathetic neurons following withdrawal of nerve growth factor (NGF). Sympathetic neurons from superior cervical ganglia of postnatal day-one Wistar rats were cultured in the presence of NGF for 24 h and then either maintained in the presence of NGF or deprived of NGF for a period of 8 h. To label the proteins being synthesised, neurons were cultured in the presence of L-[35S]methionine for a further 2 h under the same conditions but with 3% of the normal methionine concentration. Neuronal proteins were then analysed by 2-D PAGE using immobilised pH gradient (IPG) gel strips in the first dimension. For the second dimension a custom-built electrophoresis system capable of running multiple sodium dodecyl sulfate (SDS)-PAGE slab gels in a vertical configuration, with good temperature control (+/- 0.7 degrees C) was used and is described in this paper. Proteins resolved on the dried gels were visualised using storage phosphor technology and the digitised images subjected to rigorous analysis using the QUEST II software system. Seventeen proteins whose relative synthesis decreased and four proteins that increased upon NGF withdrawal were located and are documented.